2017
DOI: 10.1111/jorc.12205
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers associated with mortality in patients undergoing dialysis

Abstract: SUMMARY Background Survival for patients commencing renal replacement therapy is around 90% in the first year and 83% at two years after starting dialysis. The factors that appear to predict mortality are comorbidity and frailty associated with kidney disease, glomerular filtration rate, age and biochemical factors. Objectives To analyse the condition of patients starting renal replacement therapy, based on biomarkers commonly used in clinical practice and their association with mortality, measured 6 and 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
6
0
2
Order By: Relevance
“…The 32 studies included in this review represent a combined population of 1 083 264 new dialysis starters and 283 277 person‐years of observation for early mortality. The characteristics of these studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 32 studies included in this review represent a combined population of 1 083 264 new dialysis starters and 283 277 person‐years of observation for early mortality. The characteristics of these studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of these studies are shown in Table . Studies originating in North America accounted for the majority of observations (12 studies, population: 831559), while the remaining observations originated in Europe (10 studies, population: 93 815 patients), Asia (four studies, combined population of 46 421 patients), Australia‐New Zealand (one study; population: 23 658), Africa (three studies, population: population of 530 patients), and South America (one study, 395 participants). There was also one multinational study , involving developed countries with 86 886 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations